Cover Picture: Synthesis of a Pillar[5]arene with Both Hydroxyl and Methoxycarbonyl‐Methoxy Groups and Its Host‐Guest Complexation with a Bis(imidazolium) Salt (Chin. J. Chem. 2/2014). Issue 2 (February 2014) - Pan, Mingguang; Xue, Min
<x xml:space="preserve">Abstract</x> The cover picture shows a novel pillar[5]arene entirely with both hydroxyl and methoxycarbonyl‐methoxy groups and its host‐guest property with a bis(imidazolium) salt. Pillararene, since it was first reported in 2008, has attracted a rising interest from many supramolecular chemists. Opportunities and challenges coexist in selective functionalization of pillararenes. Our group used a facile strategy (partial oxidation and reduction) to obtain the pillar[5]arene entirely with two types of functional groups from the initial starting compound, 1, 4‐dimethoxypillar[5]arene (DMP[5]). Its self‐assembly in the solid state showed that a water molecule had triple bonding with the host, which implied its potential application in new type of proton transmembrane channels. Thanks to this regioselective preparation, the host‐guest property of this pillararene with a bis(imidazolium) salt was studied. More details are discussed in the article by Xue et al. on page 128–132.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>